Banks with Higher Levels of Fintech Adoption Exhibit Better Financial ‎Performance Than Those with Lower Levels of Adoption - Verma , Mr. Som Shekhar; Sreenu , Dr. Nenavath; Kushwaha , Dr. Gyaneshwar Singh (International Journal of Accounting and Economics Studies, 2025)
This study examines the impact of FinTech adoption on the financial performance of ‎commercial banks in India, with a particular focus on Return on Assets (ROA) as a primary ‎indicator of profitability. Drawing on a comprehensive panel dataset of Indian commercial ‎banks from 2012 to 2022, the research employs advanced econometric techniques—including ‎fixed effects, random effects, and dynamic panel models (Difference and System Generalized ‎Method of Moments)—to address endogeneity and capture both short-term and long-term ‎effects. The findings reveal that while higher levels of FinTech adoption are associated with an ‎initial, statistically significant decline in ROA—reflecting the transitional costs and operational ‎challenges of digital integration—banks with greater scale are better positioned to absorb these ‎short-term impacts and achieve superior financial outcomes over time. Traditional drivers such ‎as loan and deposit growth do not significantly influence ROA in the digital era, highlighting ‎the evolving determinants of banking success. The study validates Schumpeter’s Innovation ‎Theory and the Technology Acceptance Model, underscoring the need for strategic planning ‎and gradual implementation of FinTech solutions. Practical implications include ‎recommendations for regulatory support, digital literacy enhancement, and tailored financial ‎incentives to facilitate smoother digital transformation, particularly for smaller banks. This ‎research contributes novel empirical evidence to the limited literature on FinTech and bank ‎profitability in emerging markets and offers actionable insights for banking professionals, ‎policymakers, and financial regulators navigating the digital age‎.